AspectCost: um ambiente de gerência e acompanhamento de custos de requisitos baseados em AOP - Tocchetto, André Lopes (Universidade do Vale do Rio do Sinos, 2007)
Since the development and the necessity of new paradigms of software development with the objective of facilitating the creation of solutions for problems that are more and more complex are gradual, and considering the solution development in a classic cascade cycle (analysis, project, codification, tests and maintenance), it is possible to state that all the stages must provide a framework to contemplate the devices that are part of these new paradigms. Thus, the development of the UML is mentioned in order to represent a software that uses the development paradigm oriented to objects, which has some functionalities that are spread throughout the software, making it difficult for its implementation and consequently its the evolution. So, aiming to solve this problem, the usage of the development paradigm oriented to aspect is proposed in order to supply this lack of the paradigm oriented to object. However, there is the necessity, as previously mentioned, of all frameworks following this evolution. Theref
Keywords: computação; desenvolvimento; engenharia; linguagem; software; UML; programação orientada para aspecto; requirements; costs; Ciências Exatas e da Terra